Permasalahan Aktual Kebudayaan di Provinsi Sulawesi Tengah - Sulaiman Mamar (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2013)
ABSTRACT This paper attempts to examine the actual problems of culture in Central Sulawesi province. Central Sulawesi is one of the provinces in Indonesia with the multicultural composition of the population and inhabit a wide area with the population density is very low. It is considered to provide opportunities for cultural issues, such as: (1) the onset of degradation of cultural values, so that the culture of positive thinking poorly functioning again as a guide behavior, (2) work ethic disparities between ethnic groups in the control of strategic natural resources, (3) emergence of problems or issues of indigenous tribes native son as opposed to ethnic immigrants, (4) the habit of consuming beverages and illicit drugs which further lead to social problems such as fights between residents. The interesting thing in this paper is that the dance modero as one type of dance that has been modified in Central Sulawesi is also considered to provide opportunities for social and cultural issues. To eliminate the problem of culture, there are several approaches that need to be implemented in public life, that is (1) necessary excavation and transformation of culture positive thinking each tribe to the younger generation, (2) ethics education to the younger generation should be encouraged, both in the household and in schools, (3) multicultural education should be included in the curriculum in schools and colleges, (4) the economic empowerment of youth. Key word: modero dance, problems of culture, multicultural